Рідкісні деревні рослини в колекції ботанічного саду Львівського національного університету ім. І. Франка - Shcherbina, N.O.; Petrova, L.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Data are presented concerning composition of dendroflora composition in Botanical Gardens of I. Franko Lviv National University. The present state of rare plants of aboriginal woody species entered in the Red Book of Ukraine has been described.